INTERACTIVE POWERPOINT FOR TEACHERS - Tan King Hiyang (Penerbit UTHM, 2013)
This first edition of Interactive PowerPoint for Teachers illustrates and shares simple but yet useful instructional design ideas and application strategies for meaningful learning. The first topic highlighted the understanding on interactivity; the second topic illustrates and provides guidance on multiple navigation design. The rest of the topics demonstrate the flexibility of interactive instructional engagement. It guides the reader, step-by-steps, on the design of slides and suggests interactive application of the designed materials. Instructional design does not has to be complicated, time consuming, require higher thinking order or advance technological qualification, what is needed, is just your passion for meaningful education and a simple book that guide you through the simple process.